Courtwatching: Visibility, publicness, witnessing, and embodiment in legal activism. Issue 4 (28th January 2021) - Gill, Nick; Hynes, Jo
Abstract: Courtwatching involves grassroots efforts to observe the day‐to‐day work of decision making in justice systems, usually undertaken by activists as a way to scrutinise and challenge the power of legal professionals such as judges. This paper argues for closer attention to courtwatching in legal geographical research. Numerous courtwatching programmes exist around the world, and the first part of the paper surveys some of these, giving a sense of their diversity, the challenges they can face, and the influence that they have. The second part of the paper uses courtwatching to explore questions of visibility, publicness, witnessing, and embodiment in legal research into courts, trials, and hearings. It argues that courtwatching highlights the complexity of legal publicness, problematising the binary notion of "closed" or "open" hearings, and also raises important questions about the ethical differences between watching and witnessing. Finally, in the context of proliferating ways in which courts are becoming public via digital means of watching, such as TV and podcasts, the paper asks what difference it makes to actually be there, in the flesh, to watch legal processes. Abstract : The paper sets out what courtwatching is and gives some examples from various countries. It argues that a closer engagement with courtwatching in legal geography will yield insights into the issues of visibility, publicness, witnessing, and embodiment that surround court observations.